MANAGEMENT AND LEADERSHIP IN THE FORMATION OF ORGANIZATIONAL CULTURE (Development Service Industry Management, 2024)
The article considers the critical role of management and leadership in the formation of organizational culture, which is the basis for the successful functioning and development of any organization. It is noted that leaders not only set strategic directions and goals, but also shape values, norms and behavior, which affect every aspect of the organization.The study is based on theoretical models and empirical data that confirm that leadership style, communication strategies, and leadership behaviors have a significant impact on the cultural aspects of organizations. In particular, the following approaches to leadership are considered, as transformational and transactional leadership, and their impact on employee motivation, involvement in decision-making processes, job satisfaction, and organizational effectiveness. The article also analyzes how leaders can use different communication strategies to support and develop organizational culture. Special attention is paid to the role of feedback, open communication and emotional intelligence of leaders in creating a positive work environment.The study highlights the challenges faced by leaders in the process of changing organizational culture, in particular, resistance to change on the part of employees and the need to adapt to external changes and new technologies. In this context, it is important to develop leadership skills such as flexibility, adaptability and the ability to innovate. It is noted that effective leadership contributes to the achievement of long-term goals of the organization, increasing its competitiveness and creating a positive image both internally and externally.
Keywords: organizational culture; manager; leadership; mechanism